Predicting Behavioral Outcomes of Humans: The Role of Emotional Intelligence (Management Dynamics, 2022)
The powerful stimulator of desired human behavior is emotional intelligence. The current investigation makes an effort to look into the relative influence of emotional intelligence on the behavioral outputs of employees in diverse Bangladeshi organizations. The method of purposive sampling was used to collect responses from 412 participants. The author applied Emotional Quotient Index (EQ Index) as well as different measurement instruments to evaluate employees’ emotional intelligence and their behavioral outcomes at the workplace. The data were analyzed with descriptive statistics, Pearson correlation, and linear regression. Quantitative outcomes from this analysis demonstrated a favorable relationship between emotional intelligence and desired behavioral outcomes, specifically, group cohesion (r=0.72, p